Influence of gravity on granular soil mechanics - Katti, A.R.; Katti, D.R.; Katti, R.K. ([S.l.] : CRC Press, 2000)
This work's themes include: stress orientated themes; deformation aspects; applications for soil improvement problems; and approaches to allowable bearing capacity problems. It also contains studies on shear strength aspects of various size fractions, and guidelines for engineers.